QbD driven targeted pulmonary delivery of dexamethasone-loaded chitosan microspheres: Biodistribution and pharmacokinetic study - B.R. Asha; Prakash Goudanavar; G.S.N. Koteswara Rao; Kumaraswamy Gandla; N. Raghavendra Naveen; Shahnaz Majeed; Ravindran Muthukumarasamy (Elsevier, 2023)
Inhaling drugs, on the other hand, is limited mainly by the natural mechanisms of the respiratory system, which push drug particles out of the lungs or make them inefficient once they are there. Because of this, many ways have been found to work around the problems with drug transport through the lungs. Researchers have made polymeric microparticles (MP) and nanoparticles as a possible way to get drugs into the lungs. They showed that the drug could be trapped in large amounts and retained in the lungs for a long time, with as little contact as possible with the bloodstream. MP were formulated in this study to get dexamethasone (DMC) into the pulmonary area. The Box-Behnken design optimized microspheres preparation to meet the pulmonary delivery prerequisites. Optimized formulation was figured out based on the desirability approach. The mass median aerodynamic diameter (MMAD) of the optimized formula (O-DMC-MP) was 8.46 ± 1.45 µm, and the fine particle fraction (FPF) was 77.69 ± 1.26%. This showed that it made suitable drug delivery system, which could make it possible for MP to settle deeply in the lung space after being breathed in. With the first burst of drug release, it was seen that drug release could last up to 16 h. Also, there was no clear sign that the optimized formulation was toxic to the alveoli basal epithelial cells in the lungs, as supported by cytotoxic studies in HUVEC, A549, and H1299 cell lines. Most importantly, loading DMC inside MP cuts the amount of drug into the bloodstream compared to plain DMC, as evident from biodistribution studies. Stability tests have shown that the product can stay the same over time at both the storage conditions. Using chitosan DMC-MP can be a better therapeutic formulation to treat acute respiratory distress syndrome (ARDS).